A mechanistic study of the participation of azomethine ylides and carbonyl ylides in [3+2] cycloaddition reactions. Issue 7 (18th February 2015) - Domingo, Luis R.; Aurell, Maria J.; Pérez, Patricia
Abstract: The participation of azomethine ylides (AYs) and carbonyl ylides (CYs) in [3+2] cycloaddition (32CA) reactions has been analysed at the DFT B3LYP/6-31G(d) level. The asymmetric substitution breaks the pseudodiradical character of the simplest three-atom-components (TACs), modifying their electrophilic and nucleophilic behaviours. These TACs react quickly towards electrophilic nitroethylene. However, while the reaction with AY takes place via a zw-type mechanism, the reaction with CY appears to take place via a pr-type mechanism. A different behaviour is found in the reactivity towards the nucleophilic methyl vinyl ether. While AY presents a high activation energy, CY presents a high reactivity via a pr-type mechanism. These reactions are completely regioselective, displaying exo stereoselectivity. The present study makes it possible to establish that the substitution provokes a different reactivity pattern in these TACs; while in CYs does not substantially modify their pr-type reactivity, AYs only participate in zw-type 32CA reactions towards electrophilic ethylenes. Graphical abstract: